Temporal shifts in iso/anisohydry revealed from daily observations of plant water potential in a dominant desert shrub. Issue 2 (28th October 2019) - Guo, Jessica S.; Hultine, Kevin R.; Koch, George W.; Kropp, Heather; Ogle, Kiona
Summary: Plant species are characterized along a spectrum of isohydry to anisohydry depending on their regulation of water potential (Ψ), but the plasticity of hydraulic strategies is largely unknown. The role of environmental drivers was evaluated in the hydraulic behavior of Larrea tridentata, a drought‐tolerant desert shrub that withstands a wide range of environmental conditions. With a 1.5 yr time‐series of 2324 in situ measurements of daily predawn and midday Ψ, the temporal variability of hydraulic behavior was explored in relation to soil water supply, atmospheric demand and temperature. Hydraulic behavior in Larrea was highly dynamic, ranging from partial isohydry to extreme anisohydry. Larrea exhibited extreme anisohydry under wet soil conditions corresponding to periods of high productivity, whereas partial isohydry was exhibited after prolonged dry or cold conditions, when productivity was low. Environmental conditions can strongly influence plant hydraulic behavior at relatively fast timescales, which enhances our understanding of plant drought responses. Although species may exhibit a dominant hydraulic behavior, variable environmental conditions can prompt plasticity in Ψ regulation, particularly for species in seasonally dry climates.